Factors influencing user participation in social media: Evidence from twitter usage during COVID-19 pandemic in Saudi Arabia. (August 2021) - Mohammed, Abdulalem; Ferraris, Alberto
Abstract: With increasing frequency, people are using social media sites to obtain timely information about the world's grand challenges and this phenomenon is amplified during crises. However, little research has been conducted to determine how people participate and how their involvement can be promoted on social media sites, although the critical role played by those sites has been well documented. Based on the theory of planned behavior (TPB), this study develops and tests a theoretical model to establish the effect of several factors with survey data collected during the COVID-19 pandemic, in Saudi Arabia. The relationship was verified on a sample of 213 respondents active on Twitter, using Partial Least Square (PLS). The study found that attitude, perceived behavioural control and subjective norm affect Twitter users' active participation significantly within the context of a time of crisis. It also found a positive effect of utilitarian and hedonic values and trust. These results will provide a more comprehensive evaluation of Twitter users in grand challenges (and more specifically during a crisis) and furnish academics and managers with instructive guidance. Highlights: The study develops a model to explain why people active participation on Twitter during Covid 19. TPB framework are applied to examine antecedents of active participation behavior on Twitter during COVID 19. People are willing participants in the crisis information sharing process on Twitter. Perceived behavior control and trust were strongly influence peoples' active participation behavior. Twitter can be adapted to fit the information and knowledge needs during crisis.